Концептуальні засади діагностики можливостей будівельних підприємств до облігаційного фінансування в умовах невизначеності - Коваленко, Є. С. (Ways to Improve Construction Efficiency, 2014)
The аrticle is devoted to a question of development of methodical approach to estimation of ability of the construction enterprises (CE) to fulfill financial obligations after bonded loans. The algorithm of diagnostics of possibility of financing of the joint venture at the expense of bonds on the basis of a method of trees of classification is offered.